Arah Pembaruan Hukum Wakaf Indonesia - Miftahul Huda (Ulumuna, 2012)
By studying The Law Number 41 Year 2004 about Waqf, this paper describes the various methods and trends of waqf legal reform in Indonesia. Variety of methods of waqf legal reform in Indonesia using several methods, such as takhṣīṣ al-qaḍā, tahyīr, talfīq, and siyāsah shar‘iyyah. The trends of waqf legal reform in Indonesia leads toward a more comprehensive of understanding the law, the development of a more integrative governance of waqf, and an increase of capacity building of stronger waqf institution. With the methods and trends of waqf legal reform, efforts to create social welfare in Indonesia are possible to realized.